Central adiposity is associated with reduced cerebral perfusion: evidence from the Irish Longitudinal Study on Ageing (TILDA). (2020) - Knight, Silvin; Laird, Eamon; O'Connor, John; Newman, Louise; Kenny, Rose Anne
Abstract: Introduction: 36% the over 50s in Ireland are obese based on body mass index (BMI: reflective of fat store peripherally) while 52% are 'centrally obese' based on waist circumference (indicative of fat located viscerally). (1 ) Visceral fat is thought to be a major site for inflammatory cytokine production and has been linked to other vascular risk factors such as hypertension and diabetes, (2 ) potentially providing a mechanism for brain atrophy. (3 ) The aim of the present work was to examine associations between obesity and grey matter (GM)/white matter (WM) perfusion as measured using pseudo-continuous arterial spin labelling (pCASL) MRI. Materials and Methods: This study was embedded within the Irish Longitudinal Study on Ageing (TILDA), a nationally representative sample of > 8, 000 older adults. (4 ) At wave three, 561 participants underwent brain MRI using a 3T scanner ( Achieva, Philips, Netherlands); after exclusions, 484 participants data were included for this analysis. Cerebral blood flow (CBF [ml/100g/min]) values were calculated and their associations with BMI and waist-to-hip ratio (WHR) measures modelled using multiple linear regression. We also examined 6 groups: 'normal', 'overweight', and 'obese' as defined by BMI, with and without central obesity, as defined by WHR. (5 ) Models were adjusted for age, sex, smoking, alcohol consumption, physical activity, education, heart disease, hypertension, anti-hypertensive use, and depression. Results: The mean age was 69 years (± 7.2 years); 52% were female. Higher BMI and WHR were both related to lower GM and WM CBF: BMI per 1 SD (GM: β:-1.451, 95%CI:-2.300 to -0.607, P < 0.001; WM: β:-0. 575, 95%CI:-0. 939 to -0.210, P = 0.002) and WHR (GM: β:−1.667, 95%CI:−2.856 to −0.477, P = 0.006; WM: β:−0.688, 95%CI:−1.178 to −0.197, P = 0.006). The combination of overall obesity (BMI ≥ 30 kg/m 2 ) and central obesity (WHR > 0.85[female], > 0.90[male]) was associated with lower CBF (GM: β:-4.303, 95%CI:-7.015 to -1.591, P = 0.002; WM: β:-2.029, 95%CI:-3.185 to -0.873, P < 0.001) compared to subjects without central obesity (GM: β:-0.959, 95%CI:-6.490 to 4.572, P = 0.733; WM:β:-0.051, 95%CI:-2.060 to 1.958, P = 0.960). Discussion: Our results show that central adiposity is a risk factor for impaired cerebral perfusion independent of BMI. Recent studies have shown that accumulation of fat in this area is a risk factor for cognitive impairment (6 ) and thus this study could partly explain the vascular origins.